Cancer incidence in sites potentially related to occupational exposures: 58 years of follow-up of firefighters in the Norwegian Fire Departments Cohort - Marjerrison, Niki; Jakobsen, Jarle; Grimsrud, Tom K.; Hansen, Johnni; Martinsen, Jan Ivar; Nordby, Karl-Christian; Veierød, Marit B.; Kjærheim, Kristina (Scandinavian Journal of Work, Environment & Health, 2022)
' ' OBJECTIVES ': 'Firefighters are exposed to a variety of known and suspected carcinogens through their work. However, the association with cancer risk has limited evidence. We examined cancer incidence among firefighters in the newly established Norwegian Fire Departments Cohort restricted to sites with established associations with carcinogens encountered during firefighting. This included sites within the respiratory, urinary, and lympho-hematopoietic systems, and the skin and all sites combined. ' ' METHODS ': 'Male firefighters (N=3881) in the cohort were linked to the Cancer Registry of Norway for incident cancer cases occurring during the period 1960–2018. We calculated standardized incidence ratios (SIR) with rates for the national male population as reference, and stratified SIR analyses by period of first employment, duration of employment, and time since first employment. ' ' RESULTS ': 'Elevated risk was seen for all sites combined (SIR 1.15, 95% confidence interval 1.07–1.23). Elevated risk of urinary tract cancer was observed among firefighters who began working before 1950, and with observation ≥40 years since first employment. Risk of mesothelioma and laryngeal cancer were elevated with ≥40 years since first employment and with ≥30 years employment duration. ' ' CONCLUSIONS ': 'The observed associations between firefighting and urinary tract cancer, laryngeal cancer, and mesothelioma have been observed in some studies previously, and our results suggest the observed elevated risks are related to carcinogenic occupational exposures. Differences in risk by period of employment potentially reflect changes in exposures from improved quality and use of personal protective equipment.
Keywords: cancer; carcinogen; cohort study; firefighter; firefighting; Norwegian Fire Departments Cohort; occupational epidemiology; occupational exposure